PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID DALAM PPKn UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN BERPIKIR KREATIF PESERTA DIDIK SMA - Rike Erlande, - (2022)
This study aims to describe the development of interactive multimedia for Android-based Civics learning to increase students' learning motivation and creative thinking. This study uses the research and development design of the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) with the subjects being class X students and PPKn teachers at Islamic Senior High School Azzahrah Palembang, Senior High School 13 Palembang and Senior High School South Sumatra. The research sample for the effectiveness of the use of learning media is that students of class X IPA 1 and X IPA 3 Senior High School Islam Azzahrah use side purposive. Research instruments include observation guidelines, interview guidelines, questionnaires, and tests. The results of the study, namely: (1) The conditions for the implementation of the use of Civics learning media in Islamic Senior High School Azzahrah, Senior High School 13 Palembang and Senior High School South Sumatra have not optimally utilized Android-based digital media in Civics learning and the characteristics of students in Civics learning are still experiencing saturation and have not the existence of technological media that can arouse students' learning motivation (2) interactive multimedia for Android-based Civics learning which was developed in a feasible category based on the results of feasibility tests by media experts, material experts, and students who obtained very decent results (3) Interactive multimedia for Civics learning based on android has a significant effect on increasing learning motivation and creative thinking. The implication of using Android-based interactive multimedia in Civics learning, especially the material for insight into the archipelago, has a positive effect on increasing students' learning motivation and creative thinking. Keywords: Interactive Multimedia, Android, Learning Motivation, Creative Thinking